Plantaricin BM-1 decreases viability of SW480 human colorectal cancer cells by inducing caspase-dependent apoptosis - Wang, He; Jin, Junhua; Pang, Xiaona; Bian, Zheng; Zhu, Jingxin; Hao, Yanling; Zhang, Hongxing; Xie, Yuanhong (Frontiers in Microbiology, 2023)
Plantaricin BM-1 is a class IIa bacteriocin produced by Lactobacillus plantarum BM-1 that has significant antimicrobial activity against food-borne bacteria. In this study, a cell proliferation assay and scanning electron microscopy were used to detect changes in the viability of SW480, Caco-2, and HCT-116 colorectal cancer cells treated with plantaricin BM-1. We found that plantaricin BM-1 significantly reduced the viability of all colorectal cancer cell lines tested, especially that of the SW480 cells. Scanning electron microscopy showed that plantaricin BM-1 treatment reduced the number of microvilli and slightly collapsed the morphology of SW480 cells. Fluorescence microscopy and flow cytometry demonstrated that plantaricin BM-1 induced apoptosis of SW480 cells in a concentration-dependent manner. Western blotting further showed that plantaricin BM-1-induced apoptosis of SW480 cells was mediated by the caspase pathway. Finally, transcriptomic analysis showed that 69 genes were differentially expressed after plantaricin BM-1 treatment (p < 0.05), of which 65 were downregulated and four were upregulated. The Kyoto Encyclopedia of Genes and Genomes enrichment analysis showed that expression levels of genes involved in the TNF, NF-κB, and MAPK signaling pathways, as well as functional categories such as microRNAs in cancer and transcriptional misregulation in cancer, were affected in SW480 cells following the treatment with plantaricin BM-1. In conclusion, plantaricin BM-1 induced death in SW480 cells via the caspase-dependent apoptosis pathway. Our study provides important information for further development of plantaricin BM-1 for potential applications in anti-colorectal cancer.